Bioethanol production from finger millet (Eleusine coracana) straw - Tekaligne, Teshager Mekonnen; Woldu, Abebe Reda; Tsigie, Yeshitila Asteraye (Ethiopian Journal of Science and Technology, 2025)
The possibility of producing bioethanol from the biomass of finger millet straw was studied. The effects of temperature, acid concentration, hydrolysis time, and substrate concentration were investigated. The result showed that a maximum sugar content of 79.04 and 82.01 %w/w was achieved using phenol-sulfuric acid and Fehling method, respectively, from hydrolysis of 10 % biomass concentration at 2 % sulfuric acid, 35oC reaction temperature, and 4 days of hydrolysis time. The optimized hydrolyzate sample was fermented at optimized pH 6.0, 4 g/L yeast concentration, 32.5 oC reaction temperature, 4 days of fermentation time, and maximum of 7.28 %w/v of ethanol content was obtained using Pycnometer measurement. In general, the bioethanol achieved from FMS (7.28 %) at optimized conditions were highly promising and hence, it can be employed as an alternative lignocellulosic feedstock for bioethanol production rather than using food crops such as corn, sugarcane, etc.